Perioperative Hypercoagulability in Free Flap Reconstructions Performed for Intracranial Tumors. (5th October 2022) - Lilly, Gabriela L.; Sweeny, Larissa; Santucci, Nicole; Cannady, Steven; Frost, Ariel; Anagnos, Vincent; Curry, Joseph; Sagalow, Emily; Freeman, Cecilia; Puram, Sidharth V; Pipkorn, Patrik; Slijepcevic, Allison; et al.
Abstract : Objective(s): Patients with intracranial tumors have a higher risk of thromboembolic events. This risk increases at the time of surgical intervention. We have noted an anecdotal increase in perioperative flap thrombosis in patients undergoing free tissue transfer for intracranial tumor resection. This study aims to formally evaluate this risk. Methods: A multi‐institutional retrospective chart review was performed of patients who underwent free tissue transfer for scalp/cranial reconstruction. Perioperative thrombosis and free flap outcomes were evaluated. Results: The 209 patients who underwent 246 free tissue transfers were included in the study. The 28 free flap scalp reconstructions were associated with intracranial tumors, 19 were performed following composite cranial resections with associated dural resection/reconstruction, and 199 were performed in the absence of intracranial tumors (control group). There was a significantly higher incidence of perioperative flap thrombosis in the intracranial tumor group (11/28, 39%) when compared to controls (38/199, 19%) ( p = 0.0287). This was not seen when scalp tumors extended to the dura alone (4/19, 21%, p = 0.83). Therapeutic anticoagulation used for perioperative thrombosis (defined as intraoperative or in the immediate postoperative phase up to 5 days) was associated with a lower risk of flap failure, although this was not statistically significant ( p = 0.148). Flap survival rates were equivalent between flaps performed for intracranial pathology (93.3%) and controls (95%). Conclusion: There is an increase in perioperative flap thrombosis in patients with intracranial tumors undergoing free tissue scalp reconstruction. Anticoagulation appears to mitigate this risk. Level of Evidence: This recommendation is based on level 3 evidence (retrospective case–control studies, systematic review of retrospective studies, and case reports) Laryngoscope, 133:1103–1109, 2023 Abstract : Patients with intracranial tumors have a higher risk of thromboembolic events. A multi‐institutional retrospective chart review was performed of patients who underwent free tissue transfer for scalp/cranial reconstruction. There is an increase in perioperative flap thrombosis in patients with intracranial tumors undergoing free tissue scalp reconstruction, and anticoagulation appears to mitigate this risk.